Unequal status of equal peoples: Causes and ways to address the problem - Mutagirov, Dzhamal Z. (Advances in Social Sciences Research Journal, 2018)
Pondering over the situation in the world, and over the nature of the relations between peoples and causes of the conflicts, it is impossible not to see that the States and ruling in them circles are the source of many of them, as a rule the most negative and destructive. An impression forms here that the real politics of these ‘institutions for the protection of human and peoples ' rights, as well as their security’ (Jefferson), aims to erect on the smooth way to the humankind’s and people’s free development all sorts of bumps and obstacles, which they then ‘heroically overcome’, calling it a ‘global politics’. The main reasons for disharmony in international life and conflicts in the world so far remain inequality of individuals and peoples, and attempts of some States to perpetuate this status, on the one hand, and a natural aspiration of peoples to equality, autonomy and progress, on the other. In the article, whose author is the philosopher of history, politics and law, is shown the causes for multi-directional activities of the peoples and their States, civil and political societies, as well as possible ways to solve them. Management of global processes in accordance with the will of the peace-loving and creative labor peoples and humanity as a whole, rather than of narrow groups of politicians, traditionally guiding by the principle ‘divide and rule’, is considered as the best way to.